Opinions of Senator Morgan at the conference in Paris of the Bering Sea Tribunal of Arbitration constituted by the treaty, of February 29, 1892, between Her Britannic Majesty and the United States of America [electronic resource] : and composed of the following members: Baron de Courcel, Senator and Ambassador of France, President of the Tribunal, the Right Honorable Lord Hannen, of Great Britain, the Honorable Sir John Thompson, Minister of Justice and Attorney-General of Canada . and His Excellency Gregers Gram, Minister of State of Norway. - Morgan, John T. (John Tyler), 1824-1907; Bering Sea Tribunal of Arbitration. (Washington : G.P.O., 1893)
At head of title: Bering Sea Tribunal of Arbitration. Electronic reproduction. Mode of access: Internet. 44